2020
DOI: 10.3389/fphys.2020.00042
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance Between Interleukin-1β and Interleukin-1 Receptor Antagonist in Epicardial Adipose Tissue Is Associated With Non ST-Segment Elevation Acute Coronary Syndrome

Abstract: Parisi et al. IL-1ra and Acute Coronary Sindromes compared to Group 1 [101 pg/ml (40; 577) vs. 1344 pg/ml (155; 5327); p = 0.002]. No correlation was found between EAT levels of IL-1β and CD86 and CD64 events. Conclusion: The present study explores the levels of IL-1β and IL-1ra in the serum and in EAT of CCS and ACS patients. ACS seems to be associated to a loss of the counter-regulatory activity of IL-1ra against the pro-inflammatory effects related to IL-1β activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In addition to TNF-α, we have found that adipocytes from IGT SO people released higher levels of IL-1β and IP-10, other key cytokines in obesity and in etiology of T2D 34 . TNFα and IL-1β work together to both initiate and propagate the in ammatory process, also inducing the expression of multiple cytokines, among which IP-10 35,36 . IP-10, also known as CXCL10, has been shown to play a deleterious role in obesity as potential inhibitor of AT angiogenesis 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to TNF-α, we have found that adipocytes from IGT SO people released higher levels of IL-1β and IP-10, other key cytokines in obesity and in etiology of T2D 34 . TNFα and IL-1β work together to both initiate and propagate the in ammatory process, also inducing the expression of multiple cytokines, among which IP-10 35,36 . IP-10, also known as CXCL10, has been shown to play a deleterious role in obesity as potential inhibitor of AT angiogenesis 37 .…”
Section: Discussionmentioning
confidence: 99%
“…It is responsible for elevation of acute phase reactants such as C-reactive protein, serum amyloid A, fibrinogen, and hepcidin and inhibition of albumin synthesis 18 . IL-1ra has inhibitory roles against pro-inflammatory cytokine activation and T lymphocyte responses 21,22 . It regulates IL-1, TNFα and IFN production 22 , arguing a potential role in constraining a further increase of these cytokines in severe patients.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β is a kind of pro-in ammatory cytokines,to a certain extent,production and release of IL-1β can resistance infection,but at the same time,there are correlations with gout,rheumatoid arthritis,chronic kidney disease,atherosclerosis and so on [27][28] .Studies have demonstrated that [29] IL-1β can promote the recruitment of neutrophil in the part of in ammation so that cause gout.In addition,IL-1β can make the person produces strong pain by activation injured receptor which exist in peripheral sensory nerve system sensitively and directly.The processing and secretion of IL-1β not only can through NOD-like receptor signaling pathways,but also can by Toll-like receptor signaling pathways.When MSU crystals are identi ed by Toll-like receptor,TLRs are able to interact with MyD88,make the MyD88 activation,leading to the activation of nuclear factor kappa B (NF-κB) and enter the nucleus to produce IL-1β,cause in ammation eventually through the cascade ampli cation effect [30][31] .…”
Section: Discussionmentioning
confidence: 99%